THE INFLUENCE OF STUDENTS WITH SPECIAL NEEDS INCLUDED IN GRADE‐3 CLASSROOMS ON THE LARGE‐SCALE ACHIEVEMENT SCORES OF STUDENTS WITHOUT SPECIAL NEEDS - Demeris, Henk; Childs, Ruth; Jordan, Anne (Canadian Journal of Education/Revue canadienne de l’éducation, 2007)
This study investigates the relationship between the number of students with special needs (designated as exceptional or receiving special education services) in grade‐3 classrooms in 1997‐1998 and their achievement scores in reading, writing, and mathematics on Ontarioʹs provincial assessment with their peers without special needs. When the variance due to differences in class size and socio‐economic status was removed, the correlations between the number of students with special needs and the average class achievement scores were slightly, but significantly, positive (.05 to .07), suggesting that the presence of students with special needs does not adversely affect achievement of other students. Key words: special education, disabilities, elementary education, inclusive schools Cette étude porte sur la relation entre le nombre d’élèves ayant des besoins particuliers (désignés comme des élèves en difficulté) dans des classes de 3e année en 1997‐1998 et leurs résultats scolaires en lecture, en écriture et en mathématiques dans les examens provinciaux de l’Ontario si on les compare à leurs camarades de classe n’ayant pas de difficultés particulières. Lorsque la variance due à la taille de la classe et au statut socio‐économique est supprimée, les corrélations entre le nombre d’élèves ayant des besoins spéciaux et chaque score de rendement moyen des classes étaient légèrement mais significativement positive (0,05 à 0,07), ce qui donne à penser que la présence d’élèves ayant des besoins spéciaux n’affecte pas la performance des autres élèves. Mots clés : éducation de l’enfance en difficulté, déficiences, études primaires, écoles inclusives